Cytoplasmic MSH2 Related to Genomic Deletions in the MSH2/EPCAM Genes in Colorectal Cancer Patients With Suspected Lynch Syndrome - Dong, Lin; Zou, Shuangmei; Jin, Xianglan; Lu, Haizhen; Zhang, Ye; Guo, Lei; Cai, Jianqiang; Ying, Jianming (Frontiers in Oncology, 2021)
Abstract Background: A large proportion of patients with Lynch syndrome (LS) have MSH2 abnormalities, but genotype-phenotype studies of MSH2 mutations in LS are still lacking. The aim of this study was to comprehensively analyze the clinicopathological characteristics and molecular basis of colorectal cancer (CRC) in patients with uncommon MSH2 cytoplasmic expression. Methods: We retrospectively reviewed 4195 consecutive cases of CRC patients diagnosed between January 2015 and December 2017 at the Cancer Hospital Chinese Academy of Medical Sciences. Of the 4195 patients with CRC, 69 were indicated to have abnormal MSH2 expression through tumor immunohistochemical staining. Genetic tests, such as next-generation sequencing, large genomic rearrangement (LGR) analysis, microsatellite instability status analysis and genomic breakpoint analysis, were performed. Clinicopathological and molecular characteristics and clinical immunotherapy response were analyzed. Results: Forty-five of 69 patients were identified to have LS with pathogenic germline mutations in MSH2 and/or EPCAM. Of these LS patients, 26.7% were confirmed to harbor large genomic rearrangements (LGRs). Of note, three tumors from two unrelated family pedigrees exhibited a rare cytoplasmic MSH2 staining pattern that was found in LS patients with EPCAM/MSH2 deletions. RNA analysis showed that two novel mRNA fusions of EPCAM and MSH2 resulted in the predicted protein fusion with MSH2 cytoplasmic localization. Analyses of genomic breakpoints indicated that two novel deletions of EPCAM and MSH2 originated from Alu repeat-mediated recombination events. Our study also provides clinical evidence for the beneficial effect of the PD-1 inhibitor pembrolizumab for CRC patients that exhibit cytoplasmic MSH2 staining. Conclusion: Our study demonstrates that the rare cytoplasmic MSH2 staining pattern should be fully recognized by pathologists and geneticists. Given the specific genotype-phenotype correlation in LS screening, we advocate that all CRC patients with cytoplasmic MSH2 staining in histology should be screened for LGRs of EPCAM and MSH2.